Use of plant extracts for the protection of the plantain bunch (Musa AAB) against insects, Sucre municipality, Zulia State - Nava, Juan; Calle, Kleber; Andrade, Pedro; Vera, Nestor; Espinoza, Winston (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
Plantain producers from the Sucre municipality of Zulia state, Venezuela, have expressed concerns about improving or maintaining the quality of the bunch, seeking to protect it from damage caused by insects, thus harming its appearance for marketing. It was proposed to evaluate the effect of aqueous plant extracts from the 100 % water-plant organ mixture for the protection of the plantain bunch. A completely randomized experimental design was used with 5 treatments and 20 repetitions. The treatments were: T1: cluster without product application; T2: cluster sprinkled with garlic bulb extract (Allium sativum); T3: cluster sprinkled with hot pepper fruit extract (Capsicum spp.); T4: bunch sprayed with lemongrass (Swinglea glutinosa) leaf extract and T5: bunch sprayed with eucalyptus (Eucalyptus spp.) leaf extract. The variable that was studied was: bunch fruits without damage from insect attack. T2 and T3 presented a higher percentage of fruits without insect damage (94 and 96 % respectively), with better quality in the bunch for commercialization.